2005
DOI: 10.1677/erc.1.00861
|View full text |Cite
|
Sign up to set email alerts
|

ERβ is a potent inhibitor of cell proliferation in the HCT8 human colon cancer cell line through regulation of cell cycle components

Abstract: Several strands of evidence indicate that oestrogens exert a protective role against the development of colon cancer through indirect and direct effects on colonic epithelium. Oestrogen receptor b (ERb), the predominant ER subtype in human colon, is significantly decreased in colonic tumours compared with normal mucosa suggesting a potential role in the regulation of colon tumour growth.To investigate this hypothesis we engineered human colon cancer ERa-negative HCT8 cells in order to obtain ERb protein over-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 41 publications
7
57
1
3
Order By: Relevance
“…Limited data have shown that E 2 treatment reduces cell growth in three colon cancer cell lines, DLD-1, HCT116, and LoVo (25)(26)(27). However, the majority of cell culture studies have shown no reduction or an increase in growth in response to E 2 in colon cancer cells that are fully transformed (13)(14)(15)(16)(17)28).…”
Section: Discussionmentioning
confidence: 99%
“…Limited data have shown that E 2 treatment reduces cell growth in three colon cancer cell lines, DLD-1, HCT116, and LoVo (25)(26)(27). However, the majority of cell culture studies have shown no reduction or an increase in growth in response to E 2 in colon cancer cells that are fully transformed (13)(14)(15)(16)(17)28).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, rapid effects generated by the E2-ERb complex drive cells out of the cell cycle (Acconcia et al 2005a), representing the key to understanding the E2-induced anti-proliferative effects working both during differentiative processes and in some forms of human cancer (e.g. colon adenocarcinoma) (Weihua et al 2003, Bardin et al 2004, Paruthiyil et al 2004, Strom et al 2004, Martineti et al 2005, Koehler et al 2005. S-nitrosylation of ERa results in the selective inhibition of DNA binding to specific EREs without affecting non-genomic events in transiently transfected HeLa cells (Marino et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Preventive Exposure to Apigenin Alters Cancer ER Stress-related Genes and Signals-Endotoxin LPS as another ER stress trigger was assessed for its ability to alter eIF2␣ phosphorylation, which is a central biomarker of ER stress-induced translational arrest in HCT-8 and HCT-116 intestinal cancer cells that are frequently used as a model of inflammatory diseases and carcinogenesis (30,31) (Fig. 1, A and B).…”
Section: Resultsmentioning
confidence: 99%